Variable cardiac myosin binding protein-C expression in the myofilaments due to MYBPC3 mutations in hypertrophic cardiomyopathy. (October 2018) - Parbhudayal, R.Y.; Garra, A.R.; Götte, M.J.W.; Michels, M.; Pei, J.; Harakalova, M.; Asselbergs, F.W.; van Rossum, A.C.; van der Velden, J.; Kuster, D.W.D.
Abstract: Background: Mutations in MYBPC3 are the most common cause of hypertrophic cardiomyopathy (HCM). These mutations produce dysfunctional protein that is quickly degraded and not incorporated in the myofilaments. Most patients are heterozygous and allelic expression differs between cells. We hypothesized that this would lead to cell-to-cell variation in cardiac myosin binding protein-C (cMyBP-C, encoded by MYBPC3 gene) protein levels. Methods: Twelve HCM patients were included (six had no sarcomere mutations (HCMsmn ) and served as the control group and six harbored mutations in the MYBPC3 gene (MYBPC3mut ). Western blot and RNA sequencing analysis of cardiac tissue lysates were performed to detect overall cMyBP-C protein and mRNA levels. Cellular expression of cMyBP-C and α-actin was obtained by immunofluorescence staining. Quantification of cell-to-cell variation of cMyBP-C expression between cardiomyocytes was measured by determining the ratio of cMyBP-C:α-actin stained area of each cell. Results: Protein and mRNA analysis revealed significantly reduced cMyBP-C levels in MYBPC3mut patients compared with HCMsmn patients (0.73 ± 0.09 vs. 1.0 ± 0.15, p  < .05; 162.3 ± 16.4 vs. 326.2 ± 41.9 RPKM, p  = .002), without any sign of truncated proteins. Immunofluorescence staining of individual cardiomyocytes in HCMsmn patients demonstrated homogenous and equal cMyBP-C:α-actin staining ratio. In contrast, MYBPC3mut patients demonstrated inhomogeneous staining patterns with a large intercellular variability per patient. Coefficient of variance for cMyBP-C/α-actin staining for each patient showed a significant difference between both groups (17.30 ± 4.08 vs. 5.18 ± 0.65% in MYBPC3mut vs. HCMsmn, p  = .02). Conclusion: This is the first study to demonstrate intercellular variation of myofilament cMyBP-C protein expression within the myocardium from HCM patients with heterozygous MYBPC3 mutations.